Géographie, photographie, polygraphie : retour sur l’établissement d’une méthode d’enquête - Jordi Ballesta (EchoGéo)
From late 1960’s, in the United-States, and one decade after, in Europe, artistic works defined here as photo-geographical have deeply changed the representation of contemporary landscapes, focusing on common places and urban forms not influenced by the organizing principles of urban planning. The purpose of this article is to describe the gradual and sometimes uncertain conceptualization of a photo-geographical approach, developed from 2000 to 2011 in the academic field, to produce knowledge about the Greek vernacular landscape.